(untitled) (PANGEEA, 2025)
Between the "new education", environmental education is probably the best structured category. It has become a worldwi necessity de and already has traditions in a lot of countries of Europe. Environmental education is based on of global, integrative and systemic principles. To the understanding of these principles is the need to know that the whole world is interrelated, that every action produces a reaction. Everyone must realize and accept to take responsibility for the impact that his life has on the life of the planet.